The Reality of the Electronic Commerce Contracts in Algeria - Mezhoud, Noureddine; Megueddem, Yacine (Journal of Legal Studies and Researches, 2022)
The electronic commerce contracts today are of great importance to many Western and Arab States. Algeria, for its part, is seeking to develop such transactions through the modernization and dissemination of the country's communications network. However, this type of trade has not yet been completed, given the constraints and problems that prevent it from being implemented in the appropriate manner.